RELATIONSHIP BETWEEN POSTURAL ALIGNMENT IN STANDING BY PHOTOGRAMMETRY AND STATIC BALANCE IN CHILDREN WITH DISABILITIES - Klavina, Aija; Galeja, Zinta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
This study was executed to explore correlation between postural alignment in standing measured through photogrammetry and static balance in children with visual, hearing, intellectual and physical disability. METHODS: Participants were 34 children (age 7-12 years) including 8 children with hearing, 8 with visual, 6 with physical, and 12 children with intellectual disabilities Postural alignment in standing was measured through photogrammetry. Static balance data were obtained in 15 s bipedal stance with eyes open and eyes closed, and also in 10 s unipedal stance. A force plate was used to collect data of Centre of Pressure amplitude in anterior-posterior, medio-lateral directions and velocity. Correlation was obtained using Spearman's Rank Correlation co-efficient in SPSS software (version 19.0). RESULTS: Moderate positive correlation (r = 0.338 to r = 425; p ≤ 0.05) was found between angle of head position and angle of frontal and sagittal ASIS and PSIS level. Also, moderate positive correlation was found between angles in shoulder level and angles of the head (r = .365 to r = .453, p < .05). In assessing the static balance outcomes between the four groups, results presented significant differences in results during bipedal stance with eyes open. CONCLUSION: Degree of forward head posture correlates directly with hip and shoulder anatomical placement. Children with intellectual disability presented larger displacement of the center of pressure with more body sway observed during eyes open condition.